Fast increase in ductility and strength of Zr-based bulk amorphous alloys induced by intermittent high-frequency vibration loading. (March 2022) - Lou, Yan; Yang, Lingyun; Xv, Shenpeng; Ma, Jiang
Abstract: Intermittent high-frequency vibration loading is introduced into the Zr41.2 Ti13.8 Cu12.5 Ni10 Be22.5 bulk amorphous alloy as an ultrashort time, easy-to-obtain, nondestructive physical method to adjust its atomic arrangement and shear deformation behavior. It is found that the method of intermittent high-frequency vibration loading can make the ductility and strength of the bulk amorphous alloys increase quickly within 4 s, increasing to 5.3% and 2240 MPa, respectively. And there is a mechanical power threshold of approximately 0.43 kJ/mol. Apart from the as-cast sample, when it is less than this threshold, with the increase of amplitude and pre-pressure, the relaxation enthalpy of IHF-treated samples increases, the ductility increases, but the compressive yield strength is basically unchanged, and there is basically no precipitation of nanocrystals at the same time. When it is greater than the threshold, as the amplitude and pre-pressure increase, the relaxation enthalpy decreases, nanocrystals precipitate, the ductility and the compressive yield strength begin to decrease. Both the increase in free volume content and the appearance of nanocrystals will lead to an increase in the critical stress of the first ejection event, thereby simultaneously increasing the ductility and yield strength. It is also found that the increase in free volume content is the main factor for the increase in ductility and strength, and the appearance of nanocrystals is a secondary factor. Our findings provide a new ultrashort time method for overcoming the strength-ductility trade-off dilemma. Graphical abstract: Image 1 Highlights: The performance of the BMG treated by IHF loading can quickly be improved without adding any plasticizer within 4 s. The room temperature ductility is increased to 5.3%, and the compressive yield strength is as high as 2240 MPa. There is a mechanical power threshold of 0.43 kJ/mol for the dual-field coupling of ultrasonic amplitude and pre-pressure. Free volume content is the main factor for the increase in ductility and strength, followed by nanocrystals.